Case Report: Metastatic renal giant-cell sarcoma in an African pygmy hedgehog (Atelerix albiventris) - Díaz-Santana, Pablo; Déniz-Marrero, Javier; Gola, Cecilia; Suárez-Bonnet, Alejandro (Frontiers in Veterinary Science, 2025)
The scientific literature referring to tumors in African pygmy hedgehog (Atelerix albiventris) is expanding, enhanced by an increased lifespan under human care. This study compiles the clinical records and pathologic findings in a 2-year and 7-month-old male African pygmy hedgehog (Atelerix albiventris) with a metastatic giant-cell renal sarcoma. Metastases to the lungs, retroperitoneum, lymph nodes, pericardium, and mediastinal adipose tissue were observed. Immunohistochemical assessment with a panel of 11 antibodies (cytokeratins [AE1/AE3, CK19, and CK20], vimentin, thyroid transcription factor-1, thyroglobulin, Ki67, Iba-1, S100, synaptophysin, and CD31) was performed, yielding negative immunolabeling in the neoplastic cells. To the author’s knowledge, neoplasms arising from the kidney in African pygmy hedgehogs are rarely reported, and a metastatic giant-cell renal sarcoma has not been previously described. This case report aims to contribute to the growing body of knowledge regarding neoplasm development and help veterinary specialists with the characterization of the pathologic conditions affecting this species.